FURNITURE INDUSTRY GREEN SUPPLY CHAIN SUCCESS FACTORS: A SYSTEMATIC LITERATURE REVIEW - Peni Shoffiyati; Fesa Putra Kristianto (Jurnal Teknologi Industri Pertanian, 2025)
In recent years, Green Supply Chain Management (GSCM) has gained significant attention due to the challenges posed by climate change, primarily driven by human activities and harmful emissions. The furniture industry presents considerable potential for GSCM adoption but faces challenges, including high costs, low environmental awareness, and limited government support. This study aimed to identify critical success factors (CSFs) for GSCM implementation in the furniture industry. Using a Systematic Literature Review (SLR) methodology, articles from Scopus and Google Scholar were examined to identify key CSFs. Six CSFs were found management commitment, investment in technology and collaboration, stakeholder involvement, environmental sustainability strategy, environmental regulations and incentives, and performance assessment and monitoring. The study highlighted the importance of a comprehensive approach, outlining essential steps for GSCM implementation, such as strategy development, green practice adoption, and ongoing monitoring and evaluation. Additionally, it emphasized integrating green purchasing, internal environmental management, and forming collaborative partnerships with stakeholders. Regular evaluations were critical to track progress, align with sustainability objectives, and identify areas for improvement. The study contributes to the GSCM literature by offering practical insights and recommendations for furniture companies, including conducting a SWOT analysis, setting clear sustainability goals, collaborating with eco-friendly suppliers, and securing top management support. These findings provide valuable guidance for the furniture industry to achieve sustainability, improve efficiency, and enhance competitiveness in the global market. Keywords: critical success factors, furniture industry, Green Supply Chain Management (GSCM), Systematic Literature Review (SLR)